ANALISIS IMPLEMENTASI PENGELOLAAN TRANSAKSI NON TUNAI TERHADAP GOOD GOVERNANCE PADA PEMERINTAH KOTA METRO - Habiburrahman Habiburrahman; Herry Soedarsa Goenawan Soedarsa; Winarni Winarni (Universitas Mitra Indonesia, 2021)
Abstract The Metro City Government began implementing a non-cash transaction system in early 2017 in accordance with the Metro Mayor's Instruction Number 3 of 2017 concerning the Implementation of Non-Cash Transactions within the Metro City Government in realizing technology-based good governance For the sake of creating accountability, transparency, effectiveness and budget efficiency in government. The method of data collection in this study was through observation, interviews, questionnaires and documentation and qualitative analysis. The results showed that the hypothesis: